Extrudable polymer-polymer composites based on ultra-high molecular weight polyethylene; AIP Conference Proceedings; Vol. 1915 : Mechanics, Resource and Diagnostics of Materials and Structures (MRDMS-2017) - Panin S. V. Sergey Viktorovich; Kornienko L. A. Lyudmila Aleksandrovna; Aleksenko V. O. Vladislav Olegovich; Buslovich D. Dmitry; Dontsov (Doncov) Yu. Yuriy Vladimirovich (2017, 2017)
Title screen